MARKETING STRATEGIES TO INCREASE FISH SALES AT UD. UDIN JAYA IN MATTIRO BAJI VILLAGE, KEPULAUAN TANAKEKE DISTRICT, TAKALAR REGENCY - Sri Wahyuni; Marhawati Najib, Muhammad Rakib, Agus Syam, Asmayanti (Jurnal Salome : Multidisipliner Keilmuan, 2024)
This research aims to analyze the appropriate marketing strategies to increase fish sales at UD. Udin Jaya. The study employs a qualitative method with a case study approach using SWOT analysis. Data were obtained through interviews with the owner of UD. Udin Jaya, employees, and customers. The results indicate that UD. Udin Jaya has a focus that allows the company to leverage its strengths and opportunities, thereby generating various strategies to enhance sales at UD. Udin Jaya.